Penyelenggaraan Special Event Berlandaskan Partisipasi Masyarakat Dan Minat Wisatawan Serta Dampaknya Terhadap Peningkatan Kunjungan Wisata. (Studi Kasus Sedekah Bumi Desa Cibuntu Kabupaten Kuningan) - Subekti, Kukuh Galih (Jurnal Ilmiah Pariwisata, 2017)
T he background of this research is to know the effect of citizen participation in Sedekah Bumi Event toward the increasement of tourist to Cibuntu village in Kuningan District. Based  on  the  data  released  in  Cibuntu  from  year  2012  -  2016,  they  have  an increasement significan numbers of tourist that came to their place. The Objective of this research is 1). How did the citizen participate in Sedekah Bumi Event?. 2). How is the tourist interest during their visitation to Cibuntu Village? Especially during Sedekah Bumi Event? T his study is design by using Qualitative Research method. Qualitative data collection techniques used interview guides to be asked of informants used as a source of data by researchers. The informant qualitative data include : The Head of Cibuntu Village, Chief committe of Sedekah Bumi event, Public Relation and Marketing of Cibuntu Village, Chief of Karang Taruna Remaja,Chief of Sacatuhu and Kahuripan Hillbill, Head of the Development of Family Welfare (PKK), and the Commitee of Pascasarjana Department, n fellow students of Pascasarjana that have been went to Cibuntu Village during Sedekah Bumi was held. A nalysis  data  method  in  this  research  is  using  Participative  Observation,  Depth Interview, and Documentation. The result of this research is the indicator of interest shows that the citizen of Cibuntu Village are Good in Participation of the Event. The indicators of Tourist Interest are also Good with the point of view from the village scenery. But they wants the need of being involved to the events. The indicators of Special event are filled with hystorical meaning from the informant. But some of the tourist said that lots of the event are not quite match with the wisdom of Sedekah Bumi.